Research on the Promoting Effect of Chinese Sports Governance System on "Double Cycle" of Sports Industry in the New Era - Zongxi LI; Olena SLAVKOVA; Yong GAO (Communications of International Proceedings, 2021)
This article through the literature material method, logic analysis and other research methods to the new era of China's sports management system model is built and ACTS as a "binary" under the new pattern of sports industry were analyzed, and the relationship between research under the background of new era, a new pattern of sports enterprise in our country and the development of international and domestic law and problems, development of our country sports enterprise comprehensive, high quality to provide theoretical reference.
Keywords: New era; Sports governance system; "Double Circulation" in Sports Industry.